2015
DOI: 10.1097/ta.0000000000000681
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells increase T-regulatory cells and improve healing following trauma and hemorrhagic shock

Abstract: Background Rodent lungs undergo full histologic recovery within one week following unilateral lung contusion (LC). However, when LC is followed by hemorrhagic shock (HS), healing is impaired. We hypothesize that the intravenous administration of mesenchymal stem cells (MSC) to animals undergoing combined LC followed by HS (LCHS) will improve wound healing. Methods Male Sprague-Dawley rats (n=5-6/group) were subjected to LCHS with or without the injection of a single iv dose of 5 × 106 MSCs following return o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…We have previously shown that MSCs enhance healing after LC, resulting in complete healing at five days post-injury 17 . More recently, we reported the benefit of MSCs in healing when LC was combined with either HS or CS 15,18 , however, it was unknown if MSCs retained their therapeutic effect in this most severe injury model, LCHS/CS. We demonstrated that a single dose of MSCs given immediately after the resuscitation period reversed this HS- and CS-induced healing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that MSCs enhance healing after LC, resulting in complete healing at five days post-injury 17 . More recently, we reported the benefit of MSCs in healing when LC was combined with either HS or CS 15,18 , however, it was unknown if MSCs retained their therapeutic effect in this most severe injury model, LCHS/CS. We demonstrated that a single dose of MSCs given immediately after the resuscitation period reversed this HS- and CS-induced healing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality from ARDS ranges from 20% to 40% . Studies utilizing MSCs for ARDS have shown good therapeutic tolerance, as well as improved recovery from ventilator‐associated pulmonary injury, decreased pulmonary edema, and increased presence of peripheral regulatory T cells . Given that cell engraftment of MSCs appears to be very low, therapeutic efficacy is believed to result from anti‐inflammatory cytokines or paracrine signals produced by MSCs .…”
Section: Current Stem Cell Therapy For Organ Fibrosismentioning
confidence: 99%
“…Concordantly, it had been demonstrated that at early time points post-burn, rats treated with MSCs have decreased circulating levels of TNF-a, IL-6, white blood cells and C-reactive protein as compared to the control group [35]. In addition, MSCs have also demonstrated the ability to attenuate T cell activation and proliferation, decrease cytotoxic T cells, and increase immunosuppressive regulatory T cells [8]. Also, murine MSCs were injected intradermally in a rat burn model resulting in an increase in anti-inflammatory cytokines TGF-b and IL-10 in the blood and reduction of CD4+ and CD8+ cells in the spleen as compared to control PBS-treated rats [3].…”
Section: Discussionmentioning
confidence: 81%